2008
DOI: 10.1007/s10911-008-9103-7
|View full text |Cite
|
Sign up to set email alerts
|

IGF-I, GH, and Sex Steroid Effects in Normal Mammary Gland Development

Abstract: Although the pubertal surge of estrogen is the immediate stimulus to mammary development, the action of estrogen depends upon the presence of pituitary growth hormone and the ability of GH to stimulate production of IGF-I in the mammary gland. Growth hormone binds to its receptor in the mammary fat pad, after which production of IGF-I mRNA and IGF-I protein occurs. It is likely that IGF-I then works through paracrine means to stimulate formation of TEBs, which then form ducts by bifurcating or trifurcating and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(61 citation statements)
references
References 53 publications
2
59
0
Order By: Relevance
“…Importantly, GH and IGF-1 signalling, together with estrogens, is essential for the development of the mammary gland, particularly the terminal end-buds. It has also been found that during lactation, IGF-1 plays an important role in the maintenance of the adult mammary gland [48][49][50]. Furthermore, percent mammographic density refers to the structure of the adipose, epithelial and connective tissue in the breast [51].…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, GH and IGF-1 signalling, together with estrogens, is essential for the development of the mammary gland, particularly the terminal end-buds. It has also been found that during lactation, IGF-1 plays an important role in the maintenance of the adult mammary gland [48][49][50]. Furthermore, percent mammographic density refers to the structure of the adipose, epithelial and connective tissue in the breast [51].…”
Section: Discussionmentioning
confidence: 99%
“…GH secreted by the pituitary gland acts as an endocrine regulator in multiple tissues (52)(53)(54)(55) and elicits peripheral IGF1 by signaling through the membrane-associated GHR linked to Jak2 (56)(57)(58)(59)(60). It was shown that GH is also expressed locally in nonpituitary cells (including colon, prostate, breast, and brain), where it feeds back to membrane-associated GHR to signal in an autocrine fashion via Jak2 (61,62).…”
Section: Discussionmentioning
confidence: 99%
“…The retraction of TEBs in mutants, even in the absence of complete ductal elongation, suggested that maturation of the gland had occurred and that limited ductal arborization was a persistent and permanent phenotype. TEBs depend on signals from a variety of growth factors, including IGF-1, growth hormone and sex steroids (Kleinberg and Ruan, 2008), and these signals may also be disrupted in reeler and Dab1 mutants.…”
Section: Research Articlementioning
confidence: 99%